The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1051/0004-6361:20020803
|View full text |Cite
|
Sign up to set email alerts
|

CCD observations of Phoebe, 9th satellite of Saturn

Abstract: Abstract. In 1998 and 1999, we started observations of the 9th satellite of Saturn. We made 163 observations using the 120 cmtelescope of Observatoire de Haute-Provence, France. We used the USNO A2 catalogue of stars for the astrometric reduction. With the help of observations of optical counterparts of ICRF sources, a zonal correction to the USNO A2.0 catalogue was computed and applied to the Phoebe positions. A comparison with the most recent theories was made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
(8 reference statements)
0
12
1
Order By: Relevance
“…Also, indirect measurement is partly responsible for the poor quality since the measuring error of S 1 is incorporated into the position of Phoebe. When compared to recently published CCD observations in Veiga et al (2000) and Fienga et al (2002) as shown in Table 5, the new calibration method allows us to obtain a "clean" and more precise position of Phoebe since our observation is obtained directly from the ACT catalogue. SAT136 in our reduction is the latest ephemeris that has been developed for "CASSINI" and it is thought to be Veiga et al 2000, F+02: Fienga et al 2002 when measured with respect to the theory of Jacobson (1998).…”
Section: Positions Of Phoebe With Respect To Act1 and Comparison Withmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, indirect measurement is partly responsible for the poor quality since the measuring error of S 1 is incorporated into the position of Phoebe. When compared to recently published CCD observations in Veiga et al (2000) and Fienga et al (2002) as shown in Table 5, the new calibration method allows us to obtain a "clean" and more precise position of Phoebe since our observation is obtained directly from the ACT catalogue. SAT136 in our reduction is the latest ephemeris that has been developed for "CASSINI" and it is thought to be Veiga et al 2000, F+02: Fienga et al 2002 when measured with respect to the theory of Jacobson (1998).…”
Section: Positions Of Phoebe With Respect To Act1 and Comparison Withmentioning
confidence: 99%
“…Veiga et al (2000) and Fienga et al (2002) have published astrometric CCD observations of the 9th satellite of Saturn, Phoebe. It is well known that the astrometric calibration of a CCD image with a small field of view (for example, 5 × 5 ) is difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to its extremely faint visual magnitude (about 16.5) and to its great distance from the primary. Recently, Fienga et al (2002) pointed out that the quality of the ephemerides will decrease if no new observations are provided in the near future. The situation gives impetus to scientists to acquire new, high quality astrometric observations of this satellite.…”
Section: Introductionmentioning
confidence: 99%
“…The situation gives impetus to scientists to acquire new, high quality astrometric observations of this satellite. In recent years, several new series of accurate CCD observations of Phoebe have been published by Veiga et al (2000), Fienga et al (2002), andPeng et al (2004). Veiga et al (2000) and Fienga et al (2002) used the very high density USNO A2 star catalogue (Monet et al 1998), while Peng et al (2004 used the high accuracy ACT catalogue (Urban et al 1998) with an overlap reduction.…”
Section: Introductionmentioning
confidence: 99%